Coarsening Evolution of γ′ Phase and Failure Mechanism of Co-Ni-Al-Ti-Based Superalloys During Isothermal Aging - Zhang, Xuming; Shang, Hang; Gao, Qiuzhi; Ma, Qingshuang; Zhang, Hailian; Li, Huijun; Sun, Linlin (Frontiers in Materials, 2022)
Novel Co-based superalloys, as potentially ideal aero-engine hot section materials, have a higher temperature bearing capacity and better oxidation resistance than Ni-based superalloys. Coarsening evolution of γ′ phase and failure mechanism of Co-Ni-Al-Ti-based superalloys during the isothermal aging process at 1073 K were investigated using multiple characterizations and testing methods. The results show that γ′ phase is uniformly distributed on the γ phase matrix, and coarsening with the increase in isothermal aging time, which results in a decrease in maximum tensile strength. Furthermore, Mo element is preferred to distribute in γ′ phase and provides stronger solution strengthening effect than Cr element, which determines more excellent mechanical properties of 2Mo superalloy than that of 2Cr superalloy. The coarsening rate of γ′ phase in the 2Cr superalloy is significantly higher than that in the 2Mo superalloy. Grain boundary failure is dominant in isothermal aging, and the cracks nucleate and expand along the vertical direction of loading stress on the grain boundary. The current work suggests that the coarsening of the γ′ phase, reduction in the volume fraction of γ′ phase, and formation of ′-precipitate depleted zone (PDZ) near the grain boundary during aging controls the deterioration of mechanical properties in Co-Ni-Al-Ti-based superalloys.